Assessing impact of manufacturing and package configurations to photosensitive compounds. (2nd June 2016) - Carvalho, Thiago C.; Escotet, Megerle L.; Lin, Judy; Sprockel, Omar L.
Abstract: Determining liability of photosensitive compounds during manufacturing, packaging, and storage remains a challenge for formulation scientists prior to the confirmatory photostability studies as per International Conference on Harmonisation (ICH) Q1B guideline. The purpose of this study was to determine the effect of light exposure to bulk process intermediates and drug product in the manufacturing environment as well as to evaluate package configurations for tablets containing Compound A. Samples were analyzed for both photodegradant levels and tablet appearance. Final blend, uncoated tablets, and coated tablets were exposed to fluorescent light relevant to the manufacturing environment. Final blend presented linear photodegradant growth from 6 to 72 h of equivalent light exposure in the manufacturing environment. Change in color of uncoated tablets occurred before quantifiable levels of photodegradant were reached. The film-coated tablets did not show photodegradation above quantifiable levels or a color shift for up to 48 h. Tablets in open conditions and packaged in HPDE bottles and PVC/Aclar (clear and opaque) were exposed to light at 1 × and 3 × the cumulative light exposure as defined in the ICH Q1B using Option 2 as the light source. The results showed that photodegradation is not a concern for all package configurations investigated and that extreme light exposure may cause a slight color shift for tablets in packages made of transparent materials. Most importantly, the study design presented herein provided a framework for an end-to-end evaluation of risks of manufacturing and packaging of tablets containing photolabile compounds prior to performing confirmatory photostability studies.